RETRACTED: Improving the methodology for monitoring vegetation cover based on type segmentation - Polevschvhikova Iuliia; Svoikin Fedor; Bozhbov Vladimir; Borozna Anatoly; Taraban Maria; Sitnikov Sergey; Kaigorodova Vera (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001